“Ek sal jou heeltyd dophou.” (I'll be watching you the whole time) Surveillance and the Male Gaze in Films by Black South African Women - Smith, Tina-Louise (Centre for Film and Media Studies, 2022)
In this study I focus on the representation of women in crime films by Black South African women to understand how Black South African women directors represent women onscreen. Laura Mulvey's 1975 essay, ‘Visual Pleasure and Narrative Cinema,' on the male gaze in Classical Hollywood cinema serves as the springboard for a close textual analysis of Jyoti Mistry's Impunity (2015) and Nosipho Dumisa's Nommer 37 (Number 37) (2018). I set out to determine how Mistry and Dumisa use the camera to represent the women protagonists in the two films, and whether they reproduce, transform, or comment on the patriarchal conventions of representation. This study finds that both directors include aspects of unconventional representation in their films, but that overall, Mistry and Dumisa direct viewers to regard the women onscreen through a heterosexual patriarchal male gaze. Strikingly, in both films, this male gaze is one of surveillance. In Nommer 37 the surveillance of the woman includes the threat of punitive sexual violence, and in Impunity the woman performs her femininity for the benefit of the surveilling male gaze. Through the self-conscious application of surveillance in Impunity, Mistry also implicates the spectator in the violence meted out to the woman. I conclude that while both filmmakers comment on the position of women in society, that by and large, they reproduce patriarchal conventions without offering new ways to regard women onscreen.